The Political Ethics of Health - Weinstock, Daniel (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2010)
This paper seeks to provide an overview of some of the main areas of debate that have emerged in recent years at the interface between theories of justice and health care. First, the paper considers various positions as to what the index of justice with respect to health ought to be. It warns on practical and principled grounds against conceptual inflation of the notion of "health" as it appears in theories of distributive justice. Second, it considers how various standards according to which goods ought to be distributed in a just society apply to debates within health care.